2018
DOI: 10.1111/acer.13875
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol (EtOH)‐Related Behaviors in α‐Synuclein Mutant Mice and Association of SNCA SNPs with Anxiety in EtOH‐Dependent Patients

Abstract: Our translational study highlights a significant role of α-synuclein in components of AUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Alcohol use disorder (AUD), as a serious social and medical problem, could cause multiple damages to central nervous system (CNS) 1 . The effects of ethanol on CNS are associated not only with impaired learning and memory 2,3 but also with mental disorders, especially anxiety disorder and major depression disorder 4,5 . Animal experiments have also demonstrated that ethanol is an important risk factor for mental disorders such as anxiety‐like and depressive‐like behaviour 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol use disorder (AUD), as a serious social and medical problem, could cause multiple damages to central nervous system (CNS) 1 . The effects of ethanol on CNS are associated not only with impaired learning and memory 2,3 but also with mental disorders, especially anxiety disorder and major depression disorder 4,5 . Animal experiments have also demonstrated that ethanol is an important risk factor for mental disorders such as anxiety‐like and depressive‐like behaviour 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…1 The effects of ethanol on CNS are associated not only with impaired learning and memory 2,3 but also with mental disorders, especially anxiety disorder and major depression disorder. 4,5 Animal experiments have also demonstrated that ethanol is an important risk factor for mental disorders such as anxiety-like and depressive-like behaviour. 6,7 In addition to the impairment on the brain, ethanol exposure also significantly alters the composition and function of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In major depressive disorder (MDD), one of the prodromal features of PD, where a 30–60% comorbidity exists with all the alpha synucleopathies, is increased α-Syn expression in blood [ 13 ]. Alpha-Syn is also linked to Alcohol Use Disorder (AUD), and some genetic variants are linked to PD, AUD as well as associated disorders such as anxiety [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%